GEOLOGI GERAKAN PEMBAHARUAN ISLAM - Andi Nurhidayah; Nurul Imana; Himar; Ary Zulkarnain; M. Amin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The Islamic reform movement represents a historical and intelectual phenomenon that has evolved alongside social, political, and cultural changes within the Muslim world. This study employs a geology of thought approach to examine the historical, ideological, and theological layers that have shaped the development of Islamic reform movements over time. The research aims to trace the origins of Islamic reform, identify key figures, and analyze the contextual factors that contributed to the emergence of reformist ideas in Islam. The findings indicate that Islamic reform did not arise abruptly but emerged through a prolonged process influenced by stagnation in religious thought, colonial domination, political decline in Muslim societies, and the chalenges of modernity. Each layer of reform—ranging from the purification of doctrine and the rationalization of Islamic thought to the contextualization of Islamic teachings—reflects Muslim responses to the conditions of their respective eras. Through the geology of thought approach, this study provides a comprehensive understanding that Islamic reform movements are dynamic, multilayered, and continuously evolving in response to both internal and external chalenges facing the Muslim community.